Spiro metric Tests and Thyroid Hormone Concentrations in sample of Iraqi Patients with Chronic Obstructive Pulmonary Disease. - Weheeb, Muhanned A.; Sultan, Kassim M.; Al.Obaidy, Muhammed W. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Chronic obstructive pulmonary disease (COPD) is a preventable disease with some significant extra pulmonary effects that may contribute to the severity in individual patients.. The systemic manifestations of COPD include a number of endocrine disorders , such as those involving the pituitary, the thyroid , the gonads, the adrenals and the pancreas. The mechanisms by which COPD alters endocrine function are incompletely understood but likely involve hypoxemia , hypercapnia , systemic inflammation and glucocorticoid administration. Objective: To evaluate the relationship between pulmonary function tests and thyroid gland function in patient with chronic obstructive pulmonary disease (COPD). Subjects and Methods: Cross sectional study was done in Baghdad teaching hospital from April 2012 to October 2012 in respiratory outpatient. Thirty eight patients were included in the study (36 male and 2 females) who had stable COPD , thyroid function tests and FEV1% were done to all of them. Patients were classified into four groups according to GOLD criteria: mild COPD ( > 80) FEV1% , moderate (80 – 50)%, severe ( 50 – 30)% and very severe < 30%. Results: one patient has decreased level of TSH , one patient has decreased T3 hormone and one patient has increased free T3 hormone level, all other patient had normal thyroid hormones levels. The results of study showed no significant changes in thyroid hormones concentrations with COPD and its severity. Conclusion: We found no significant changes in thyroid hormones in patients with COPD, and any changes that occur in TFT in these patients are may be due to other causes than COPD.